Evaluation of Meatal Stenosis Following Neonatal Circumcision - Mahmoudi, Hossein (Urology Journal, 2009)
Introduction: Meatal stenosis almost always develops following neonatal circumcision, and it usually does not become apparent until the child is toilet trained. The present study was conducted to determine the value of diagnostic ultrasonography in patients with meatal stenosis. Materials and Methods: A descriptive study was performed on 120 patients with meatal stenosis, referred to Naghavi Hospital, Kashan, Iran, from July 2000 to March 2002. Symptoms and findings on physical examination were recorded for every patient, ultrasonography of the urinary tract, and urinalysis and urine culture were also performed. Results: Mean age of the patients was 2.5 years (range, 3 months to 6 years). The common symptoms were dysuria (35%), decreased urine caliber (33.3%), and bloody spotting (15%), while 26.6% of the patients were asymptomatic. Paraclinical findings were microscopic hematuria (17.5%), bacteriuria (1.6%), and ureteral duplication (0.8%). No case of obstructive uropathy was detected by ultrasonography. Conclusion: Meatal stenosis rarely causes obstructive uropathy. Hence, urinary tract ultrasonography is rarely necessary, unless symptoms persist after meatotomy.